Wireless communications empowered by reconfigurable intelligent surfaces: Model-based vs model-free channel estimation - Li Wei; Chongwen Huang; George C. Alexandropoulos; Ahmet M. Elbir; Zhaohui Yang; Zhaoyang Zhang; Marco Di Renzo; Mérouane Debbah; Chau Yuen (Journal of Information and Intelligence, 2023)
Reconfigurable intelligent surfaces (RISs) are lately being attractive for their great potential in future sixth generation wireless communications (6G), which is attributed to their affordable energy consumption and easy integration. However, the large numbers of low-cost reflecting elements comprising RISs impose challenges for channel acquisition in various RIS-based wireless applications, such as RIS-enhanced orthogonal frequency-division multiplexing and multi-user multiple-input multiple-output systems. In this article, we first overview the state-of-the-art RIS hardware architectures designed to assist channel estimation for RIS-empowered wireless communication systems. We also overview existing channel estimation approaches, which are categorized into model-based and model-free techniques, and discuss their advantages and limitations depending on the RIS deployment. Design challenges with RIS-empowered systems in terms of hardware and other parameter limitations are presented, together with future research directions for channel estimation in RIS-based wireless systems, such as RISs with extremely large numbers of elements, multi-hop communications with RISs, and frequency division duplexing for high mobility systems.